Implementing and analyzing performance assessments in teacher education - Many, Joyce; Bhatnagar, Ruchi (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
Teacher education has long relied on locally-developed assessments that lack reliability and validity. Rigorous performance-based assessments for preservice teachers have been advanced as one possible way to ensure that all students receive instruction from a high-quality teacher. Recently, performance-based assessments have been developed which focus on the application of knowledge of teaching and learning in a classroom setting. Our book explores factors related to the implementation of teacher performance assessments in varying state and institutional contexts. The contributors, teacher educators from across the country, focus on what was learned from inquiries conducted using diverse methodologies (quantitative, qualitative, self-studies, and mixed methods). Their research encompassed faculty, supervisors, cooperating teachers, and students' perceptions and concerns of teacher performance assessments, case studies of curricular reform and/or resistance, analyses of experiences and needs as a result of the adoption of such assessments, and examinations of the results of program alignment and reform. The chapters showcase experiences which occurred during high-stakes situations, in implementation periods prior to high-stakes adoption, and in contexts where programs adopted performance assessments as an institutional policy rather than as a result of a state-wide mandate.
Keywords: Teachers -- Training of -- United States -- Evaluation.; Student teachers -- Rating of -- United States.; First-year teachers -- Rating of -- United States.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books